Local Initiatives in the Province and Municipal Laws in Algeria - Abdelmadjid , Slama (Dirasat: Shari’a and Law Sciences, 2021)
The study of local initiatives in the law of local provinces and municipalities in Algeria in terms of their scope has great importance on local development as a strategic goal, so this research paper will highlight these points to determine the extent of their effectiveness in the end and the impact that we have reached. The study leads to the conclusion that these initiatives, unfortunately, do not have the force of compulsion or reparation as an initiative that does not go beyond this meaning, thereby emptying it of its content, not to mention the ambiguity, its scope, its limits, and the overlapping and conflicts of its competent authorities which leads to its ineffectiveness, except in rare cases that necessitates setting a real legal framework for serious local initiatives that guarantees mandatory power for it to ensure that it is presented by its embodiment following what is legally prescribed, and the need to separate the authorities concerned with these initiatives in terms of distributing powers among them and making them clear and applicable. The descriptive approach and the analytical approach have been adopted in this study. The results of the study were as follows: the vibration and ambiguity of local initiatives in the laws of regional groups necessarily lead to their ineffectiveness only rarely and are ineffective in most cases, and to solve this problem, the elements of compulsion and sanction must be available to achieve the effectiveness of local initiatives.